(untitled) (REMUNOM, 2025)
Traumatic dental injury (TDI) stands as one of the most prevalent dental emergencies in Primary Health Care (PHC), requiring immediate and competent clinical management to prevent functional, aesthetic, and psychosocial sequelae. This cross-sectional study aimed to identify the main challenges faced by dentists working in Brazil’s Unified Health System (SUS) regarding TDI management in public primary care units in the states of Rio de Janeiro and Minas Gerais. Data were collected through a structured electronic questionnaire completed by 27 professionals. Results showed that 92.6% of facilities frequently lacked essential materials and equipment, and only 18.5% of professionals systematically applied clinical protocols. Additionally, 85.2% received no financial support for continuing education, and 59.3% bore full responsibility for their professional development. Interprofessional collaboration was deemed insufficient by 33.3% of participants, and 88.9% reported the absence of institutional training on TDI. The study concludes that urgent public health policies are required to strengthen the SUS dental care network by promoting integrated strategies among managers, health professionals, and academic institutions, ensuring equity and quality in TDI care.